2009
DOI: 10.1080/09638280802243286
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial adjustment to multiple sclerosis: exploration of identity redefinition

Abstract: The findings provide insight into the psychological process of identity redefinition associated with adjusting to MS. Given this, interventions should target role/identity re-examination to assist individuals with MS in better managing the disease and enjoying life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
134
1
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(146 citation statements)
references
References 43 publications
8
134
1
3
Order By: Relevance
“…Maintaining a high social-emotional QoL should be a goal for those with MS and their social environment, as also shown by various other studies (Boeije et al, 2002;Charmaz, 1983;Grech et al, 2016;Irvine et al, 2009;Kralik et al, 2003;Madan & Pakenham, 2014;Reynolds & Prior, 2003;Rintell, Frankel, Minden, & Glanz, 2012;Strober, 2016). It appears beneficial to offer personalized interventions oriented toward unique needs of women and men to improve their QoL.…”
Section: Quality Of Life and Personalized Psychological Interventionsmentioning
confidence: 98%
See 2 more Smart Citations
“…Maintaining a high social-emotional QoL should be a goal for those with MS and their social environment, as also shown by various other studies (Boeije et al, 2002;Charmaz, 1983;Grech et al, 2016;Irvine et al, 2009;Kralik et al, 2003;Madan & Pakenham, 2014;Reynolds & Prior, 2003;Rintell, Frankel, Minden, & Glanz, 2012;Strober, 2016). It appears beneficial to offer personalized interventions oriented toward unique needs of women and men to improve their QoL.…”
Section: Quality Of Life and Personalized Psychological Interventionsmentioning
confidence: 98%
“…Most studies of MS have been conducted with women only, or have lacked the power to make gender comparisons (Irvine et al, 2009;Kralik et al, 2003;Reynolds & Prior, 2003). Themes that have arisen among studies of only women have revealed topics such as missing being able to wear high heels, potentially indicating a sense of lost femininity (Irvine et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative studies using mixed MS type samples showed that whereas the MS diagnosis is met with a negative reaction, after the first few years, many people reported finding a way to preserve usual activities (Dennison, Yardley, Devereux, & Moss-Morris, 2011;Irvine, Davidson, Hoy, & Lowe-Strong, 2009). Qualitative studies also showed that as functional limitations increase in MS, people find it difficutl or impossible to identify new, fulfilling activities and they may give up efforts to adjust altogether (Lexell, Lund, & Iwarsson, 2009;Wilkinson & das Nair, 2013).…”
Section: Running Head: Adjustment In Progressive Msmentioning
confidence: 99%
“…Meervoudige Sklerose (MS) is ʼn verlammende, degeneratiewe, inflammatoriese siekte van die sentrale senuweestelsel (SSS) en een van die mees algemene neurologiese siektes onder volwassenes (Bhattacharya, Mishra & Tiwari 2012;Irvine, Davidson & LoweStrong 2009 (Reipert 2004). Verder kom fisieke en kognitiewe gestremdheid, asook die verlies van blaas of dermbeheer en seksuele disfunksies, algemeen voor (Bagert, Camplair & Bourdette 2002;Bhattacharya e.a.…”
Section: Inleidingunclassified